Preparation method of graphite negative electrode material with high energy density and fast charging for lithium battery
Through graphene modification and catalytic graphitization technology, the energy density and fast charging performance of the graphite anode material of lithium battery are improved, and the problem of insufficient energy density and fast charging ratio in the existing technology is solved, and high energy density and high magnification are achieved. The results are taken into account.
Patent Information
- Application Number
- CN202210609143.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-31
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2042-05-31
AI Technical Summary
The existing lithium battery graphite anode materials have shortcomings in terms of energy density and fast charging ratio, which are difficult to meet the needs of high energy density and high magnification.
Using graphene modification and catalytic graphitization synergistic technology, through mechanical fusion, isostatic molding and high-temperature graphitization treatment, graphene negative electrode materials with high energy density and fast charging are prepared, and graphene is used to form conductive networks and catalyst pore building and enhance the production of catalysts. Conductivity and fast charging performance.
It significantly improves the energy density and fast charging performance of lithium batteries, reduces the use of conductive agents, increases the capacity of active substances in the battery space, reduces production costs, and is suitable for large-scale production.
Smart Images

Figure 220531123247 
Figure BDA0003671412160000081 
Figure BDA0003671412160000091
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium batteries, and in particular to a method for preparing a lithium battery graphite negative electrode material with high energy density and fast charging. Background Art
[0002] Lithium-ion batteries have the characteristics of high operating voltage, high energy density, wide operating temperature, long cycle life, no memory effect, and environmental friendliness. They are widely used in power battery fields such as automobiles and electric bicycles, energy storage fields such as power grids, industrial energy storage, household energy storage and communication energy storage, and 3C digital fields such as smart phones, laptops, smart wearable devices, and mobile power supplies.
[0003] The current commercial lithium battery negative electrode materials are mainly modified natural graphite and artificial graphite. Although the preparation technology is quite mature, the requirements for lithium-ion batteries are gradually increasing, especially in terms of energy density and fast charging. At present, the charge and discharge rate of graphite is not high, and the energy density is low. In order to improve the charge and discharge rate, some manufacturers will modify the graphite. For example, Chinese patent CN201711333907.X prepares high-capacity and high-rate composite graphite negative electrode materials by granulating and graphitizing carbon microspheres and artificial graphite single particles, but the charging rate can only reach 1-2C, and the charging rate is still not high, which is difficult to meet the use requirements of higher rates; in order to improve the energy density of lithium batteries, some manufacturers use a single-particle graphitized material and a secondary-particle graphitized material for mixing. For example, Chinese patent CN 201910987301.0 mixes a single-particle graphitized material with a secondary-particle graphitized material to obtain a high-energy-density graphite negative electrode material mixed with a single particle and a secondary particle, but the capacity is only below 358mAh / g, which cannot meet the demand for high energy density. Therefore, it is necessary to improve the existing lithium battery graphite negative electrode materials. Summary of the invention
[0004] In view of this, the present invention aims to address the deficiencies in the prior art, and its main purpose is to provide a method for preparing a graphite negative electrode material for lithium batteries with high energy density and fast charging. The prepared graphite negative electrode material has the performance of high rate and high energy density at the same time, and can meet the use requirements of high rate and high energy density at the same time.
[0005] To achieve the above purpose, the present invention adopts the following technical solutions:
[0006] A method for preparing a lithium battery high energy density and fast charging graphite negative electrode material, comprising the following steps:
[0007] (1) Mixing
[0008] The coke raw material, catalyst, conductive agent and binder crushed to a certain particle size are added into a mechanical fusion machine according to a certain mass ratio and processed for 5-20 minutes to obtain a mixture material;
[0009] (2) Briquetting
[0010] The mixture obtained in step (1) is placed in a rubber mold, and placed in an isostatic pressing machine for molding at a pressure of 100-300 MPa to obtain an isostatically pressed block;
[0011] (3) Graphitization
[0012] The isostatically pressed block obtained in step (2) is placed in a graphitization furnace for high-temperature graphitization treatment at 3000-3200° C. for 20-50 hours. After crushing and screening, a high energy density and fast charging graphite negative electrode material is obtained.
[0013] As a preferred embodiment, the mass ratio of the coke raw material, catalyst, conductive agent and binder in step (1) is 1:(0.05-0.1):(0.005-0.03):(0.05-0.15).
[0014] As a preferred solution, the coke raw material in step (1) is one or a mixture of crushed petroleum coke and needle coke, with D50=5-12 μm and ash content ≤0.5%.
[0015] As a preferred embodiment, the binder in step (1) is one or a mixture of coal-based asphalt and oil-based asphalt, and has a softening point of 50-200°C.
[0016] As a preferred solution, the conductive agent in step (1) is graphene, the carbon content of which is above 99.5%, the number of layers is 1-10, and the sheet diameter D50 is 0.2-3 μm.
[0017] As a preferred embodiment, the catalyst in step (1) is one or more of silicon, silicon compounds, iron, and iron compounds, and its purity is ≥95%.
[0018] Compared with the prior art, the present invention has obvious advantages and beneficial effects. Specifically, it can be seen from the above technical solution that:
[0019] The present invention improves energy density by graphene modification and catalytic graphitization. First, the modified graphene is evenly distributed in the graphite phase, and the contact performance of the two is good, which greatly enhances the conductivity of the graphite material and its coating layer. The amount of conductive agent added can be reduced in the battery manufacturing process, and even the use of conductive agent can be completely omitted, so that more active substances can be placed in the limited battery space, increasing the energy density of the battery. Secondly, catalytic graphitization can further increase the capacity of graphite to more than 360mAh / g, thereby further improving the energy density of the battery. At the same time, the synergistic effect brought by the catalyst pore formation during graphene modification and catalytic graphitization improves the fast charging performance: graphene forms a rich conductive network between graphite and granulation coating, reduces system impedance and battery polarization, improves conductivity, and enhances the rate characteristics of the battery. The catalyst will volatilize during graphitization and leave rich pores, providing a convenient path for the diffusion of lithium ions, and further improving the fast charging performance. This preparation method has simple process, convenient operation, and less production equipment, thereby further reducing costs, facilitating promotion and application, and is suitable for large-scale production.
[0020] In order to more clearly illustrate the structural features and effects of the present invention, the present invention is described in detail below in conjunction with specific embodiments. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a SEM test image of the high energy density and fast charging graphite negative electrode material prepared in Example 1. DETAILED DESCRIPTION
[0022] The present invention discloses a method for preparing a lithium battery high energy density and fast charging graphite negative electrode material, comprising the following steps:
[0023] (1) Mixing
[0024] The coke raw material, catalyst, conductive agent and binder crushed to a certain particle size are added into a mechanical fusion machine in a certain mass ratio and processed for 5-20 minutes to obtain a mixture material; the mass ratio of the coke raw material, catalyst, conductive agent and binder is 1:(0.05-0.1):(0.005-0.03):(0.05-0.15); the coke raw material is one or a mixture of crushed petroleum coke and needle coke, D50=5-12μm, ash content ≤0.5%; the binder is one or a mixture of coal-based asphalt and oil-based asphalt, with a softening point of 50-200°C; the conductive agent is graphene, with a carbon content of more than 99.5%, a layer number of 1-10 layers, and a sheet diameter of D50=0.2-3μm; the catalyst is one or more of silicon, silicon compounds, iron, and iron compounds, and its purity is ≥95%.
[0025] (2) Briquetting
[0026] The mixture obtained in step (1) is placed in a rubber mold and placed in an isostatic pressing machine for molding at a pressure of 100-300 MPa to obtain an isostatically pressed block.
[0027] (3) Graphitization
[0028] The isostatically pressed block obtained in step (2) is placed in a graphitization furnace for high-temperature graphitization treatment at 3000-3200° C. for 20-50 hours. After crushing and screening, a high energy density and fast charging graphite negative electrode material is obtained.
[0029] The present invention is described in detail below with reference to specific embodiments.
[0030] Example 1
[0031] (1) Mixing
[0032] A coke raw material, a catalyst, a conductive agent and a binder crushed to a certain particle size are added into a mechanical fusion machine in a certain mass ratio and processed for 5 minutes to obtain a mixture material; the mass ratio of the coke raw material, the catalyst, the conductive agent and the binder is 1:0.05:0.005:0.15; the coke raw material is crushed petroleum coke, D50=5-12μm, and ash content ≤0.5%; the binder is coal-based asphalt, and the softening point is 50-200°C; the conductive agent is graphene, and its carbon content is more than 99.5%, the number of layers is 1-10 layers, and the sheet diameter D50 is 0.2-3μm; the catalyst is silicon, and its purity is ≥95%.
[0033] (2) Briquetting
[0034] The mixture obtained in step (1) is placed in a rubber mold and placed in an isostatic pressing machine for molding at a pressure of 200 MPa to obtain an isostatically pressed block.
[0035] (3) Graphitization
[0036] The isostatically pressed block obtained in step (2) is placed in a graphitization furnace for high-temperature graphitization treatment at 3100° C. for 30 hours. After crushing and screening, a high-energy-density and fast-charging graphite negative electrode material is obtained.
[0037] Example 2
[0038] (1) Mixing
[0039] The coke raw material, catalyst, conductive agent and binder crushed to a certain particle size are added into a mechanical fusion machine in a certain mass ratio and processed for 20 minutes to obtain a mixture material; the mass ratio of the coke raw material, catalyst, conductive agent and binder is 1:0.1:0.03:0.05; the coke raw material is crushed needle coke, D50=5-12μm, ash content ≤0.5%; the binder is oil-based asphalt, with a softening point of 50-200°C; the conductive agent is graphene, with a carbon content of more than 99.5%, a layer number of 1-10 layers, and a sheet diameter of D50=0.2-3μm; the catalyst is a silicon compound, and its purity is ≥95%.
[0040] (2) Briquetting
[0041] The mixture obtained in step (1) is placed in a rubber mold and placed in an isostatic pressing machine for molding at a pressure of 150 MPa to obtain an isostatically pressed block.
[0042] (3) Graphitization
[0043] The isostatically pressed block obtained in step (2) is placed in a graphitization furnace for high-temperature graphitization treatment at 3050° C. for 56 hours, and after crushing and screening, a high-energy-density and fast-charging graphite negative electrode material is obtained.
[0044] Example 3
[0045] (1) Mixing
[0046] The coke raw material, catalyst, conductive agent and binder crushed to a certain particle size are added into a mechanical fusion machine in a certain mass ratio and processed for 16 minutes to obtain a mixture material; the mass ratio of the coke raw material, catalyst, conductive agent and binder is 1:0.07:0.02:0.1; the coke raw material is a mixture of crushed petroleum coke and needle coke, D50=5-12μm, ash content ≤0.5%; the binder is a mixture of coal-based asphalt and oil-based asphalt, with a softening point of 50-200°C; the conductive agent is graphene, with a carbon content of more than 99.5%, a layer number of 1-10 layers, and a sheet diameter D50=0.2-3μm; the catalyst is iron, and its purity is ≥95%.
[0047] (2) Briquetting
[0048] The mixture obtained in step (1) is placed in a rubber mold and placed in an isostatic pressing machine for molding at a pressure of 100 MPa to obtain an isostatically pressed block.
[0049] (3) Graphitization
[0050] The isostatically pressed block obtained in step (2) is placed in a graphitization furnace for high-temperature graphitization treatment at 3180° C. for 27 hours, and after crushing and screening, a high-energy-density and fast-charging graphite negative electrode material is obtained.
[0051] Example 4
[0052] (1) Mixing
[0053] A coke raw material, a catalyst, a conductive agent and a binder crushed to a certain particle size are added into a mechanical fusion machine in a certain mass ratio and processed for 9 minutes to obtain a mixture material; the mass ratio of the coke raw material, the catalyst, the conductive agent and the binder is 1:0.08:0.01:0.15; the coke raw material is crushed petroleum coke, D50=5-12μm, and ash content ≤0.5%; the binder is coal-based asphalt, and the softening point is 50-200°C; the conductive agent is graphene, and its carbon content is more than 99.5%, the number of layers is 1-10 layers, and the sheet diameter D50 is 0.2-3μm; the catalyst is an iron compound, and its purity is ≥95%.
[0054] (2) Briquetting
[0055] The mixture obtained in step (1) is placed in a rubber mold and placed in an isostatic pressing machine for molding at a pressure of 300 MPa to obtain an isostatically pressed block.
[0056] (3) Graphitization
[0057] The isostatically pressed block obtained in step (2) is placed in a graphitization furnace for high-temperature graphitization treatment at 3080° C. for 33 h. After crushing and screening, a high-energy-density and fast-charging graphite negative electrode material is obtained.
[0058] Example 5
[0059] (1) Mixing
[0060] A coke raw material, a catalyst, a conductive agent and a binder crushed to a certain particle size are added into a mechanical fusion machine in a certain mass ratio and processed for 12 minutes to obtain a mixture material; the mass ratio of the coke raw material, the catalyst, the conductive agent and the binder is 1:0.09:0.018:0.06; the coke raw material is crushed needle coke, D50=5-12μm, and ash content ≤0.5%; the binder is oil-based asphalt, and the softening point is 50-200°C; the conductive agent is graphene, and its carbon content is more than 99.5%, the number of layers is 1-10 layers, and the sheet diameter D50 is 0.2-3μm; the catalyst is silicon, and its purity is ≥95%.
[0061] (2) Briquetting
[0062] The mixture obtained in step (1) is placed in a rubber mold and placed in an isostatic pressing machine for molding at a pressure of 265 MPa to obtain an isostatically pressed block.
[0063] (3) Graphitization
[0064] The isostatically pressed block obtained in step (2) is placed in a graphitization furnace for high-temperature graphitization treatment at 3000° C. for 50 hours, and after crushing and screening, a high-energy-density and fast-charging graphite negative electrode material is obtained.
[0065] Example 6
[0066] (1) Mixing
[0067] The coke raw material, catalyst, conductive agent and binder crushed to a certain particle size are added into a mechanical fusion machine in a certain mass ratio and processed for 18 minutes to obtain a mixture material; the mass ratio of the coke raw material, catalyst, conductive agent and binder is 1:0.1):0.02:0.12; the coke raw material is crushed needle coke, D50=5-12μm, ash content ≤0.5%; the binder is coal-based asphalt, with a softening point of 50-200°C; the conductive agent is graphene, with a carbon content of more than 99.5%, a layer number of 1-10 layers, and a sheet diameter of D50=0.2-3μm; the catalyst is an iron compound, and its purity is ≥95%.
[0068] (2) Briquetting
[0069] The mixture obtained in step (1) is placed in a rubber mold and placed in an isostatic pressing machine for molding at a pressure of 285 MPa to obtain an isostatically pressed block.
[0070] (3) Graphitization
[0071] The isostatically pressed block obtained in step (2) is placed in a graphitization furnace for high-temperature graphitization treatment at 3200° C. for 50 hours. After crushing and screening, a high-energy-density and fast-charging graphite negative electrode material is obtained.
[0072] Comparative Example 1
[0073] In step (1), graphene is not added, and other conditions are the same as those in Example 1.
[0074] Comparative Example 2
[0075] In step (1), no catalyst was added and other conditions were the same as those in Example 1.
[0076] The performance tests of the products obtained in the above examples and comparative examples are carried out below.
[0077] SEM Testing
[0078] The product obtained in Example 1 was tested by SEM using Hitachi SU1510.
[0079] Electrochemical performance test
[0080] In order to detect the performance of the negative electrode material of the lithium ion battery of the negative electrode material of the present invention, the above embodiments and comparative examples were tested by the half-cell test method. The negative electrode material of the above embodiments and comparative examples: SBR (solid content 50%): CMC: Super-p = 95.5: 2: 1.5: 1 (weight ratio), added with appropriate amount of deionized water to make a slurry, coated on copper foil and dried in a vacuum drying oven for 12 hours to make a negative electrode sheet, the electrolyte is 1M LiPF6 / EC+DEC+DMC=1: 1: 1, the polypropylene microporous membrane is the diaphragm, the counter electrode is a lithium sheet, and assembled into a battery. The constant current charge and discharge experiment was carried out in the LAND battery test system, the charge and discharge voltage was limited to 0.01-3.0V, and the data was collected and controlled by a computer-controlled charge and discharge cabinet to measure the rebound of the electrode sheet under full charge. The test results are shown in Table 1.
[0081] Table 1
[0082]
[0083]
[0084] It can be seen from Table 1 that the prepared lithium-ion battery negative electrode material has excellent capacity performance, cycle performance, first charge and discharge efficiency and rate performance. Figure 1 It can be seen that graphene is evenly distributed between graphite and the granulated coating layer, acting as a conductive network, and the porosity of the surface is caused by the volatilization of the catalyst. This porous morphology and the modification effect of graphene synergistically promote the excellent fast charging performance.
[0085] The above description is only a preferred embodiment of the present invention and does not limit the technical scope of the present invention. Therefore, any slight modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a graphite negative electrode material for a lithium battery with high energy density and fast charging, characterized in that: The following steps are involved: (1) Mixing Add the coke raw material, catalyst, conductive agent and binder crushed to a certain particle size into a mechanical fusion machine according to a certain mass ratio and process for 5 minutes to obtain a mixture material; the mass ratio of coke raw material, catalyst, conductive agent and binder is 1:0.05:0.005:0.15; the coke raw material is crushed petroleum coke, D50=5-12μm, ash content ≤0.5%; the binder is coal-based asphalt, with a softening point of 50-200℃; the conductive agent is graphene, with a carbon content of more than 99.5%, a layer number of 1-10 layers, and a sheet diameter of D50=0.2-3μm; the catalyst is silicon, with a purity of ≥95%; (2) Briquetting The mixture obtained in step (1) is placed in a rubber mold, and placed in an isostatic pressing machine for molding at a pressure of 200 MPa to obtain an isostatically pressed block; (3) Graphitization The isostatically pressed block obtained in step (2) is placed in a graphitization furnace for high-temperature graphitization treatment at 3100° C. for 30 hours. After crushing and screening, a high-energy-density and fast-charging graphite negative electrode material is obtained.
Citation Information
Cited By
Preparation method of high-energy-density fast-charging negative electrode material
CN116588924A
Preparation method of high-energy-density fast-charging negative electrode material
CN116588924B
Graphite composite material and its preparation method and application
CN118954498B
High-energy-density fast-charge composite negative electrode material, preparation method and application thereof
CN121172072A